ChemInform Abstract: Phosphine‐ and Hydrogen‐Free: Highly Regioselective Ruthenium‐Catalyzed Hydroaminomethylation of Olefins. Issue 1 (January 2015) - Guelak, Samet; Wu, Lipeng; Liu, Qiang; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract A new, highly regioselective (n:iso up to <99:1) hydrogen‐ and ligand‐free hydroaminomethylation of terminal alkenes is reported.